GEOGRAPHICAL ANALYSIS OF FOREST FLORA OF THE CENTRAL CISCAUCASIA - I. L. Ivanov; I. N. Guseva (Юг России: экология, развитие, 2014)
Abstract. Aim. Forest flora of the Central Ciscaucasia in General is a relict, geographically situated in the steppe zone. Composing flora elements have different types of habitats, concentrated in the natural physical-geographical unit where isolated from the main habitats. Comparative analysis of the geographic, ecological and systematic components of forest flora will provide data about the correlation of these parameters identify the leading group. Location. The Central CiscaucasiaMethods. We made the geographical and systematic ranges of forest flora of the Central Ciscaucasia and their comparative analysis is conducted.Results. Geographical analysis of forest flora of the Central Ciscaucasia revealed 16 geographical elements, grouped in 6 categories, among which is the predominant group of boreal geographical elements. It is established that the leading geographical elements are Euro-Caucasian, Caucasian and Sub-Caucasian, numbering 189 species, and are half of the flora. Comparison with ecological spectrum showed that the sequence geographical elements completely different, here leading positions are occupied Northern species as ecologically more conservative, and the Caucasian demonstrate ecological plasticity. In a systematic relation matched warheads geographical and systematic spectra. The scope of the results. The results may be used in comparative Floristics, in its theoretical part in adjusting themodels of the Genesis of the flora.Conclusions. Thus, half of the geographical elements of the forest flora of the Central Ciscaucasia are linked in their distribution of Caucasian floristic province (Euro-Caucasian, Caucasian and Sub-Caucasian). These same geographical elements to predominate in the head part of the spectrum families. Most geographical elements have low ecological plasticity species, their components, do not go beyond the forest plant association, but geographical elements head part of the geographical range are the most ecologically plasticity.